Analysis re-entrant honeycomb auxetic structure for lumbar vertebrae using finite element analysis - Ai’man A’siqin, Zulkefli; Muhammad Hazli, Mazlan; Takano, Hiromitsu; Abdul Halim, Abdullah; Muhammad Hilmi, Jalil; Mohammad Azeeb, Mazlan (Asian Research Publishing Network (ARPN), 2024)
Lumbar spinal fusion is a frequent surgical solution among people who are experiencing severe persistent lower back pain. One treatment option is Lateral Lumbar Interbody Fusion (LLIF) surgery. In the medical field, finite element analysis (FEA) can be used to predict the best surgical plan. LLIF surgery involves implanting an interbody cage into the disc space, which may potentially move to regain the disk height while helping stabilize the vertebral bones. In this study, FEA was applied using Mechanical Finder software (MF) to develop a 3D spine model lumbar vertebrae of the fourth and fifth lumbar vertebrae (L4 - L5) with the interbody cage design. The cage was made of polyether ether ketone (PEEK) and designed using Solidworks software. Given the auxetic structure's outstanding energy absorption capabilities, a re-entrant auxetic structure core with a novel sandwich panel was implanted between the lumbar vertebrae L4 and L5, as determined by CT scans using MF software. The model was analyzed in MF to assess the strength and fracture risk analysis of the interbody cage, with the results compared to mechanical properties values obtained by applying compression load (1000 N) to simulate spinal movements. Stress and strain distribution rates were exhibited when applying a force of 1000 N. The findings underscore the relevance of cage design, namely the surface endplate, in mitigating undesirable occurrences associated with cage sinking. To attain enough strength under typical conditions, a lumbar cage with a re-entrant auxetic construction has been proposed. for lumbar vertebrae using finite element analysis